The total money makeover: a proven plan for financial fitness (Brilliance Audio on compact disc, ,, 2009)
"Ramsey offers a bold, no-nonsense approach to money matters, providing not only the how-to but also a grounded and uplifting hope for getting out of debt and achieving total financial health. Ramsey debunks the many myths of money (exposing the dangers of cash advance, rent-to-own, debt consolidation) and attacks the illusions and downright deceptions of the American dream, which encourages nothing but overspending and massive amounts of debt. "Don't even consider keeping up with the Joneses," Ramsey declares in his typically candid style. "They're broke!" This book isn't theory. It works every single time. It works because it is simple. It works because it gets to the heart of the money problems: you"--Publisher's description.
Total money makeover challenge , Denial: I'm not that out of shape , Debt myths: Debt is (not) a tool , Money myths: (Non) secrets of the rich , Two more hurdles: Ignorance and keeping up with the Joneses , Save $1,000 fast: Walk before you run , Debt snowball: Lose weight fast, really , Finish the emergency fund: Kick Murphy out , Maximize retirement investing: Be financially healthy for life , College funding: Make sure the kids are fit too , Pay off the home mortgage: Be ultrafit , Build wealth like crazy: Arnold Schwarzedollar, Mr. Universe of money , Live like no one else , More total money makeover stories , Budgeting forms.

Sizzling Sixteen (Stephanie Plum mysteries, 16, 1, 2010)
New York Times best selling author Janet Evanovich presents the sixteenth installment in the Stephanie Plum series, a collection of romantic adventures featuring the ditzy yet lovable New Jersey bounty hunter, Stephanie Plum.

A financial picture of Colorado agriculture: Part II (Service in action, no. 3.754,, 1983)
Description Not Provided

Pirates of the Caribbean : Dead Man's Chest (Pirates of the Caribbean, 2,, 2006)
Captain Jack owes a blood debt to the legendary Davy Jones, who captains the ghostly Flying Dutchman. Unless Jack can find a way out, he will be cursed to an afterlife of eternal servitude and damnation.
Walt Disney Pictures presents, Jerry Bruckheimer Films ; Second Mate Productions ; produced by Jerry Bruckheimer ; written by Ted Elliott & Terry Rossio ; directed by Gore Verbinski.

44 Charles Street: a novel (Brilliance Audio on compact disc, ,, 2013)
Owner of a struggling art gallery and newly separated from her boyfriend, Francesca Thayer does the math and then the unimaginable. She puts out an advertisement for boarders, and soon her Greenwich Village house becomes a whole new world.

Confessions of a shopaholic (Shopaholic series, 1, 1, 2009)
In this all-too-true debut novel, Kinsella chronicles one woman's hilarious efforts to overcome her expensive--if stylish--addiction to shopping. The author has brilliantly tapped into our collective consumer conscience to deliver a tale of our times and a heroine who grows stronger every time she weakens. Becky Bloomwood is bored to death writing for Successful Saving. So, with a handsome credit line from her bank, she liberates herself the best way she knows how -- by shopping! Think of it as an investment, she tells herself. But, soon she is buried in bank notices and cursed VISA bills.

Debt cures "they" don't want you to know about (Equity Press, Debt Cures, 2008)
Kevin Trudeau blows the lid off the banking and credit card industries, exposing the greatest rip off of our citizens in this nation's history, then offers solutions to your debt problems while at the same time keeping more money in your pocket and using credit to build your wealth.
A license to steal , The credit shakedown , Hanky panky , Eliminate your debt! , Negotiate! , Cut your rate! , Fighting back , Highest points wins , The report , Knowing the score , Show me the money , Two magic words, X3 , Class is now in session , Home is where the start is , No bankruptcy , Big business , Stealing candy from babies , Three ring circus , Slaying the dragons , Stop debt collectors cold , Achieving wealth , Rebuilding credit , Building more wealth , Free money! , More free money , O Canada , It's a wrap!

Sunset review, regulation of debt adjusters (Colorado Department of Regulatory Agencies, Office of Policy & Research, 1993)
Description Not Provided

Little Dorrit (Oxford world's classics, ,, 2012)
The daughter of an imprisoned debtor suffers injustices of nineteenth-century English society.

Mulberry Hollow (Riverbend romance, 2, 1, 2022)
"Avery Robinson decided to be a physician after helplessly watching her mother lose a battle with a terrible disease. Now at risk of developing the same illness, Avery guards her heart from love. She's driven to protect her loved ones as a workaholic doctor in the tiny mountain town of Riverbend Gap, North Carolina. Contractor Wes Garrett is hiking the Appalachian trail, in memory of the man who died saving his life, when an illness racks his body. After an agonizing fifteen-mile hike to Avery's clinic, he collapses on her doorstep. He recovers to find himself in debt again, this time to a beautiful doctor. When he decides to help her renovate a rundown carriage house, the obstacles to their attraction sprout like weeds--starting with the woman waiting for Wes at the end of the trail. Will he be able to relinquish the debt he owes his best friend? And will Avery find the courage to risk everything for love? The second book in Denise Hunter's popular Riverbend Romance series explores what it might be like to live fearlessly and free."--

Little Dorrit (Project Gutenberg Literary Archive Foundation, 1997)
Description Not Provided

A Week From Sunday (Tantor Media, Inc., Warner Books, Thorndike Press, Grand Central Publishing, 2007)
"Adrianna Moore has just had a double shock: the death of her father and the discovery that he has left his entire estate to his lawyer. The lawyer, a repulsive social climber, tells her that to regain her inheritance, she must marry him a week from Sunday. Adrianna takes off, driving desperately to a new life. Caught in a violent rainstorm, she collides with an oncoming truck. Quinn Baxter, the driver of the truck, demands repayment for his lost cargo. They reach a bargain: she will live in his home, tutor his bedridden younger brother and play piano in Quinn's tavern to pay off her debt. Drawn to the rugged Quinn, challenged by the interaction with the tavern patrons, she also must deal with an intractable foe--Quinn's housekeeper who is scheming to become his wife. And all the while, the spurned lawyer is following Adrianna's trail, determined to find her and force her to marry him."--Publisher description.

The spender's guide to debt-free living: how a spending fast helped me get from broke to badass in record time (HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, HarperCollins Publishers, 2016)
In 2009, young photographer Anna Newell Jones was rapidly suffocating under the weight of too much debt. An inveterate 3spender,4 she was in way over her head, to the tune of almost $24,000. She knew her debt was only going to get worse if she didn2t take action, but she didn2t know where to look for help. On a whim, Anna decided to go on a spending fast, an idea she heard in passing but knew little about. Creating her own method, she learned what worked and what didn2t and wrote about it on her blog, AndThenWeSaved.com. Amazingly, Anna was able to eliminate all $23,605.10 of her debt in only fifteen months! She was interviewed in Forbes, Self, Glamour, Good Housekeeping, and the Chicago Tribune.

Thieves of Weirdwood (Thieves of Weirdwood, 1, 1, 2021)
Wally Cooper and Arthur Benton, who resorted to thievery to pay off family debts, unwittingly find themselves at the center of a battle between the Fae and the mages tasked with protecting humanity.

Widows (Twentieth Century Fox Home Entertainment, 2019)
The story is about four women who do not share anything in common apart from the debts their dead husbands left behind. They all take fate into their own hands concerning all the criminal activities their husbands were involved in. The four women become close friends and find a way that will give them a secure and a conducive environment. They end up working together and conspires to collaborate a future on their rapports to avoid being involved in the crimes committed by their husbands.

Someone Else's Bucket List (Kensington Publishing Corp, HighBridge, Kensington Books, 2023)
A bingeworthy, bittersweet, sisterly P.S. I Love You for the digital age, Someone Else's Bucket List follows shy Jodie Boyd after the untimely death of her outgoing, hugely successful Instagram influencer sister, Bree-and Bree's last wish: that Jodie complete her bucket list. Instructed by a series of videos left by Bree, Jodie takes on the terrifying challenge as the world watches. The venture will not only change Jodie's life, but save the family-and possibly others-from staggering medical debt. Perfect for fans of Josie Silver and Rebecca Serle. My dying wish is for you to finish my bucket list. I refuse to die without knowing this list will be completed. And I refuse to die without knowing my family will be okay . . . Jodie Boyd is a shy and anxious twenty-something, completely unsure what to do with her life. Her older sister, Bree, is an adventurous, globe-trotting, hugely successful Instagram influencer with more than a million followers. She's the most alive person Jodie knows-up until Bree's unfathomable, untimely death from Leukemia. The Boyds are devastated, not to mention overwhelmed with medical debt. But Bree thought of everything-and soon, Jodie is shocked by a new post on her sister's Instagram feed. The first of many Bree recorded in secret, the post foretells a jaw-dropping challenge for Jodie: to complete Bree's very public bucket list. From "Fly over Antarctica," to "Perform a walk-on cameo in a Broadway musical," if Jodie does it-and keeps all Bree's followers-a corporate sponsor will pay off the staggering medical debt. If she gains followers, the Boyds won't be the only ones to benefit. It's crazy. It's terrifying. It's impossible, immoral even, to refuse. So, despite the whole world watching, Jodie plunges in, never imagining that in death, her sister will teach her how to live, and that the last item on the list-"Fall in love"-may just prove to be the easiest.

Principles for navigating big debt crises (Bridgewater, Avid Reader press, 2022)
Dalio believes that most everything happens over and over again through time so that by studying their patterns one can understand the cause-effect relationships behind them and develop principles for dealing with them well. In this 3-part research series, he does that for big debt crises and shares his template in the hopes reducing the chances of big debt crises happening and helping them be better managed in the future. The template comes in three parts: 1) The Archetypal Big Debt Cycle (which explains the template), 2) 3 Detailed Cases (which examines in depth the 2008 financial crisis, the 1930's Great Depression, and the 1920's inflationary depression of Germany's Weimar Republic), and 3) Compendium of 48 Cases (which is a compendium of charts and brief descriptions of the worst debt crises of the last 100 years). Whether you're an investor, a policy maker, or are simply interested, the unconventional perspective of one of the few people who navigated the crises successfully, Principles for Navigating Big Debt Crises will help you understand the economy and markets in revealing new ways.

Hollywood dead: a Sandman Slim novel (Sandman Slim, 10, 1, 2018)
Back from Hell courtesy of a deal with the evil power brokers, Wormwood, Sandman Slim has a limited amount of time to do their bidding before his partially-living body dies again, this time with no hope of him returning.

Sorry we missed you (Zeitgeist Films, 2020)
Ricky and his wife Abby, who lost their home in the 2008 financial crash, are desperate to get out of their economic distress. When Ricky gets the opportunity to be his own boss as a delivery driver, they trade in their only asset, Abby2s car, for a new white van and the dream that Ricky can work his way up to owning his own franchise. But the couple find their lives are quickly pushed further to the edge by an unrelenting work schedule, a ruthless supervisor, and the needs of their children.

Random (Blackstone Publishing, Akashic Books, 2023)
Two weeks before his twenty-first birthday, Las Vegas native Bobby Ingersoll finds out he’s inherited a crushing gambling debt from his scumbag father. The debt is owed to an even scummier bag named Fraser Ruphart who oversees his bottom-rung criminal empire from the classy-adjacent Trump International Hotel. Bobby’s prospects of paying off the note, which comes due the day he turns twenty-one, are about as dim as the sign on the tower’s façade. The two weeks pass in the blink of a (snake) eye, but before Bobby’s luck runs out, he stumbles upon enough cash to pay Ruphart off and change his family’s fortune. More importantly, he finds himself with a new, for lack of a better word, faith. Bobby does not consign his big break to a “higher power"—what Penn Jillette hero ever could? Instead, he devises and devotes himself to Random, a philosophy where his life choices are based entirely on the roll of his “lucky” dice. What follows is a hilarious exploration into not so much what defines us as what divines us when we give over every decision—from what to eat to whom to marry to how or when to die—to the random fall of two numbered cubes. Combining the intellectual curiosity of Richard Dawkins with the humor and grit of an Elmore Leonard antihero, Jillette’s up-on-his-luck Ingersoll is the character we need to help us navigate the chaos of the post-truth era. Well, unless his roll runs cold.